Penerapan Metode Profile Matching Untuk Menentukan Starting Lineup Tim Futsal Nadera Jaya Sukabumi - Al-Fadirohim, Moch Aldi; Prajoko; Pambudi, Agung (Jurnal Teknik Informatika UNIKA Santo Thomas, 2022)
Futsal is one of the most popular sports in Indonesia. Futsal is a sport that is played with all aspects of simplicity which refers to the sport of football. The problem in determining the starting lineup by the current futsal coach is that it is not efficient, they still use feeling and player development charts in each exercise. Therefore we need a system as a tool for selecting the starting lineup, making it easier for coaches in the lineup selection process. Profile matching method whose calculation mechanism assumes that there is an ideal level of predictor variables that must be met by the subject under study, not a minimum level that must be met. The advantage of the Profile Matching method is that one of the most appropriate methods used in the comparison process between individual competencies into the competencies of a position so that differences in competencies can be known. The final result of this research produces a system that can help the potential value of a player so that the coach has a benchmark in classifying the category of each player who will be the starting lineup in each competition.